Effect of lifting the sweeps on bottom trawling catch efficiency on the Northeast arctic cod trawl fishery - Sistiaga, Manu Berrondo; Grimaldo, Eduardo; Herrmann, Bent; Larsen, Roger B.; Tatone, Ivan (Sintef fiskeri og havbruk AS, 2014)
Fuel consumption and environmental concerns have led bottom trawlers fishing for cod (Gadus morhua) in the Barents Sea to use semi-pelagic doors. However, this change may affect fish herding and consequently the catch efficiency of the gear. In this study we compared the catch efficiency of two different setups where the sweep length with bottom contact was different. This setup also enabled us to estimate the herding efficiency of the sweeps on the seabed. The data for this study were collected using the alternate haul method and analyzed using a new method for unpaired data. We estimated that the setup with the lifted sweeps captured on average 33% fewer cod than the setup that kept the sweeps at the seabed. The loss of catch for cod was length independent and significant for a length span between 41 and 104 cm. When sweeps were lifted above the seabed, herding was negatively impacted and fish were lost; in contrast, when on the seabed, the sweeps were able to herd (on average) 45% of the cod into the catch zone of the gear. Lifting the trawl doors from the seabed is touted as a positive development for this fishery. However, our results show that lifting the doors and consequently the sweeps can lead to substantial catch losses. Finally, the study highlights the importance of carefully evaluating the positive and negative potential consequences of introducing changes in a fishing gear.